Postoperative Rehabilitation Comparison of Patients After Anterior Cervical Disectomy and Autograft Fusion With or Without Smoothing the Donor Site Defect - Caryn Anasthasya Naomi Sihite; Ridha Dharmajaya (Sumatera Medical Journal, 2025)
Background: Anterior cervical discectomy and autograft fusion (ACDF) is the gold standard of surgical treatment for HNP cervical. However, donor site complication has found in the form of pain that could lead to disability. The edge of the donor site defect can initiate pain may reduce patient’s quality of life. High ambulation can be earned by smoothing the donor site defect. Objective: The purpose of this study is to determine the quality of patient rehabilitation after ACDF with autograft between smoothing group and non-smoothing group. Methods: This cross-sectional study was conducted at the Adenin Adenan Hospital Medan. Patients who had undergone ACDF with autograft in 2015–2020 were assessed for their disability at the first, third, and sixth months postoperatively using Barthel Index. Total sampling method was used with inclusion and exclusion criteria. Results: There were 41 respondents in this study, 20 people in the non-smoothing group and 21 people in the smoothing group. The disability experienced by the smoothing group was less than the non-smoothing group at each month of measurement, but only significant (p<0.05) at the sixth month. Conclusion: Conclusions of this study was disability and rehabilitation outcomes in the smoothing group were better than in non-smoothing group.